Evaluación de la expresión de celo y el tratamiento con GNRH en la inseminación de vacas cebú con cría al píe - Avellán Chávez, Jamil Porfirio (2022)
The objective of this research was to evaluate the expression of heat and GnRH treatment in cows without heat on the pregnancy rate in fixed-time artificial insemination (IATF) programs. Zebu cross cows were used with calf at the foot (N = 868) greater than two to six calvings, average weight of 440 ± 40 kg and body condition between 2.5 to 4. A conventional protocol was used that consisted of the insertion of an intravaginal device with progesterone for seven or eight days, estradiol benzoate (EB) on Day 0 and estradiol cypionate (ECP) on Day 8. Cows without heat were randomly divided with or without GnRH at the time of passage of the sleeve, and received IATF 8 hours later. The data were analyzed using the InfoStat generalized and mixed linear models procedure. It was found that both the presentation of heat and GnRH in the animals that did not show heat improved pregnancy (56% those with heat vs. 48% those without heat; and 58% those with GnRH vs 34% those without GnRH; P = 0.04). It is concluded that the expression of heat increases the pregnancy rate in IATF programs, and the treatment with GnRH to animals that do not show heat after removal of the device with progesterone increases pregnancy and reduces the negative effect of non-expression of heat. zeal.